Impact of Clinical and Histo-Pathological Prognostic Factors on T1-2N0-1 Oral Tongue Carcinoma - Pichit Sittitrai (2018)
To determine predictive factors which affect local and regional recurrence of T1-2N0-1M0 oral tongue carcinoma (OTC). Records of 42 patients with T1-2N0-1 M0 OTC were reviewed. The clinical characteristics, histo-pathological data, disease recurrence and survival rate were analyzed. Descriptive statistics and Kaplan-Meier survival analysis were used. The median follow up was 38 months. The 2-year overall survival and disease-free survival rates were 85. 7 and 55. 6 % respectively. At the 2 year analysis, there were surgical margin <5 mm (p value = 0. 01), tumor thickness >7 mm (p value = 0. 03), perivascular and perilymphatic invasion (p value = 0. 01) affected on local recurrence and perivascular and perilymphatic invasion were also predictors for regional recurrence (p value = 0. 04). The surgical margin status, tumor thickness, perivascular and perilymphatic invasion represented significant predictive factors for local recurrent OTC. Postoperative adjuvant therapy should be considered in these groups. © 2012 Association of Otolaryngologists of India.